Cholinergic regulation of object recognition memory - Okada, Kana; Hashimoto, Kouichi; Kobayashi, Kazuto (Frontiers in Behavioral Neuroscience, 2022)
Object recognition memory refers to a basic memory mechanism to identify and recall various features of objects. This memory has been investigated by numerous studies in human, primates and rodents to elucidate the neuropsychological underpinnings in mammalian memory, as well as provide the diagnosis of dementia in some neurological diseases, such as Alzheimer’s disease and Parkinson’s disease. Since Alzheimer’s disease at the early stage is reported to be accompanied with cholinergic cell loss and impairment in recognition memory, the central cholinergic system has been studied to investigate the neural mechanism underlying recognition memory. Previous studies have suggested an important role of cholinergic neurons in the acquisition of some variants of object recognition memory in rodents. Cholinergic neurons in the medial septum and ventral diagonal band of Broca that project mainly to the hippocampus and parahippocampal area are related to object location memory. Cholinergic projections from the nucleus basalis magnocellularis innervating the entire cortex are associated with object recognition memory for its identification. Especially, cholinergic projected regions, such as the perirhinal cortex and prefrontal cortex, are involved in other variations of object recognition memory, including object-in-place memory and object recency. In addition, experimental studies using rodent models for Alzheimer’s disease have reported that neurodegenerative lesion in the central cholinergic system causes a deficit in object recognition memory. Elucidating how various types of object recognition memory are regulated by distinct cholinergic cell groups is necessary to clarify the neuronal mechanism for recognition memory and the development of therapeutic treatments for dementia.